Acute Painful Horner's Syndrome Revealing Eagle's Syndrome: A Report of Two Cases. (4th July 2022) - Maamouri, Rym; Ouederni, Meriem; Oueslati, Yassin; Mbarek, Chiraz; Chammakhi, Chiraz; Cheour, Monia
ABSTRACT: Eagle's syndrome (ES) is characterised by an abnormally elongated styloid process. It remains a complex pathology and the ophthalmological symptoms are relatively rare. Herein, we report two cases who presented to our clinic with unilateral and painful Horner's syndrome. Computed tomography scanning showed the presence of ES with unilateral extrinsic compression of the sympathetic plexus by the styloid.